Obtaining distributional information on Indian Ocean cetaceans: suggestions based on an Indian network experience - Sathasivam, Kumaran; Natarajan, K. S. (J. Cetacean Res. Manage., 2023)
The understanding of the occurrence and distribution of cetaceans in the Indian region is largely based on information that has been incidentally obtained from strandings and bycatches. An attempt was made to compile such data systematically. The resultant database has been made widely accessible by hosting it on the internet. To improve the quality of information collected, identification aids were published on the same website. A stranding booklet was also created, mainly for the use of individuals and organisations with limited access to the internet. The ‘spare capacity’ of individuals and organisations was used to gather information and also to prepare the website and booklets, so that little or no expense was incurred. Recommendations are made regarding the collection of distributional data from the Indian Ocean.